Pengaruh Kompetensi Manajerial Kepala Sekolah dan Lingkungan Kerja terhadap Mutu Layanan pada Masa Pandemi di SMK Cendikia Muslim Nanggung Bogor - Zainal Abidin; Anita Puspita (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Service quality is the quality of interaction between one person and another by promoting customer satisfaction. This study aims to determine the effect of principal managerial competence and the work environment on the services quality during the pandemic period in SMK Cendikia Muslim Nanggung. This research was conducted at SMK Cendikia Muslim Nanggung. The number of samples taken was 39 teachers, with a non-probability sampling method with a saturated sample technique. The research approach used is a quantitative approach with a survey method, the data collection technique used is a non-test in the form of a questionnaire with 5 (five) alternative answers. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it was found that the principal managerial competence and work environment simultaneously or collectively had a positive effect on service quality. This shows that the stronger the influence of the principal managerial competence and the work environment together, the resulting service quality will increase.